Business Planning Strategy for Etnowellness SPA Products in Pinge Tourism Village, Tabanan Regency - Komang Shanty Muni Parwati; I Gusti Made Riko Hendrajana; Dewa Putu Kiskenda Erwanda Putra (Enrichment : Journal of Management, 2022)
The existence of a tourist village should provide benefits that have economic value that can be directly felt by the people in the Pinge tourism village. This study discusses how SPA activitiesas part of how to care for health and beauty, it offers products in the form of products from the inside and outside, seen from the type of use. And the business potential of the ethno wellness spa must receive attention. The method that will be used in this research is to look for potential and opportunities to develop SPA ethno wellness products by collecting relevant information through a survey of villagers. Then by using qualitative methods, survey results through interviews, distributing questionnaires and research matters will directly discuss the topic of business development strategy for ethno spa products as one of the tourism products of the Pinge tourism village.Selection of respondents in this study will use purposive sampling. In collecting data, the research team will use the method of observation, interviews, and documentation. Observations will be carried out to identify potential, available materials, marketing strategies that can be developed in the Pinge tourism village. Interviews will be carried out together with villagers, pokdarwis and village officials. Documentation will be used to collect documents and archives related to local wisdom content around the Pinge tourism village. The results of data collection will be analyzed through three stages, namely data reduction, data display, and drawing conclusions. The results of the data analysis will be recipes for ethno wellness spa products based on local wisdom.